2002
DOI: 10.1359/jbmr.2002.17.3.544
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Calcium Intake and Physical Activity With Bone Density and Size in Premenopausal and Postmenopausal Women: A Peripheral Quantitative Computed Tomography Study

Abstract: The purpose of this cross-sectional study was to examine the impact of long-term physical activity (PA) and calcium intake on non-weight-bearing radius and weight-bearing tibia. ). The distal end and shaft regions of the radius and tibia were evaluated with peripheral quantitative tomography (pQCT). For the shaft regions, bone mineral content (BMC), cortical cross-sectional area (CoA), cortical density (CoD), and bone strength index, that is, 1-11.9% of the density-weighted section modulus (BSI) were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 39 publications
7
30
0
2
Order By: Relevance
“…Twelve studies met the necessary criteria for inclusion in our review [12][13][14][15][16][17][18][19][20][21][22][23]; four randomized controlled trials, one non-randomized trial, three cross-sectional studies, and four prospective cohort studies. These studies are summarized in Tables 1 through 3 according to study design. Sample sizes varied across studies ranging from 98 to 234 participants in the controlled trials, 126 to 239 participants in the cross-sectional studies, and 31 to 208 participants in the prospective investigations.…”
Section: Study Design Sample Size and Statistical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies met the necessary criteria for inclusion in our review [12][13][14][15][16][17][18][19][20][21][22][23]; four randomized controlled trials, one non-randomized trial, three cross-sectional studies, and four prospective cohort studies. These studies are summarized in Tables 1 through 3 according to study design. Sample sizes varied across studies ranging from 98 to 234 participants in the controlled trials, 126 to 239 participants in the cross-sectional studies, and 31 to 208 participants in the prospective investigations.…”
Section: Study Design Sample Size and Statistical Methodsmentioning
confidence: 99%
“…Cross-sectional and prospective studies reported on associations between exercise participation and bone outcomes, and for the most part also adjusted for pertinent confounders (all of the cross-sectional studies and two of the prospective studies [15,21]). Eight of 12 studies assessed postmenopausal women between the ages of 50 and 71 years [12,13,[18][19][20][21][22][23]. One study included postmenopausal women under the age of 50 years [14] and three studies examined a more elderly population (women over the age of 72 years) [15][16][17].…”
Section: Study Design Sample Size and Statistical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, [6]. 골다공증 예방 법으로 적당량의 칼슘섭취 및 영양소를 섭취하면서 적절 한 체중부하 운동을 평생 지속하는 것이 가장 현실적인 접근이며 [7] 이차성 부갑상선 기능항진증은 골이영양증 의 발생에 관여한다 [8].…”
Section: 서론unclassified
“…Vor allem im Rahmen von Interventionsstudien wurden die Studienteilnehmer nur über wenige Jahre aktiv verfolgt. In Beobachtungsstudien erfolgte auch häufig nur eine retrospektive Querschnittsbefragung, in der die vergangene KA sowie die Durchführung bestimmter Sportarten bis zurück in das Kindes-und Jugendalter erfasst wurde [1,13,44,55,64,67,95,98]. Allerdings zeigten die Studien unterschiedliche Ergebnisse.…”
Section: Nachhaltigkeitunclassified